Geração Y: característica de um novo ouvinte - Magnoni, Antonio Francisco [UNESP]; Miranda, Giovani Vieira [UNESP] (My University, 2012)
The aim of this study is to present the main features in relation to the consumption of meédia, especially the radio, the current teenagers who make up the so‑called Generation Y or Generation Internet. The members of this generation are people in forming in socio‑cultural, educational, psychological and professional, under heavy influence of the cultures of com‑ puting, audiovisual communication and also the economic and cultural globalization. For this reason, they represent a strategic public for research on reception and media culture.

O presente artigo objetiva apresentar as principais características em relação ao consumo de mídia, especialmente o radiofônico, dos atuais adolescentes que compõem a denominada Geração Y, ou Geração da Internet. Esses são pessoas em formação sociocultural, educacio‑ nal, psicológica e profissional, sob intensa influência das culturas da informática, da comuni‑ cação audiovisual e também da globalização cultural e econômica, e, por isso, representam um público estratégico para as pesquisas sobre recepção e cultura midiática.
Generation Y: characteristics of a new radio listener
Keywords: Communication; Generation Y; Content radio; Reception; Comunicação; Geração Y; Recepção; Rádio